The Power of Home: How Family Literacy Shapes Early Reading Development in Young Children - Amrina Sari, Riski; Septiana, Dita (Universitas PGRI Adi Buana Surabaya, 2026)
Literacy is widely recognized as a foundational skill that enables children to engage meaningfully in society and learning. Among the factors shaping literacy development, family literacy plays a crucial role by providing children with early exposure to language, print, and supportive interactions at home. This study aims to investigate the impact of family literacy practices on early reading development in young children. Using a qualitative case study design, data were collected through interviews and observations in two families with children aged four and five. The findings reveal that both children demonstrated strong literacy skills for their age, including the ability to read alphabetically, recognize Arabic letters, and count numbers. The five-year-old child showed advanced competence supported by formal schooling and parental reinforcement. At the same time, the four-year-old, despite not yet attending school, displayed comparable abilities through consistent parental engagement, storytelling, and religious practices at home. These results indicate that family literacy significantly contributes to children’s emergent reading skills, complementing or even compensating for formal education. The study concludes that family literacy not only supports children’s technical abilities in reading and numeracy but also fosters motivation, confidence, and cultural identity as learners. Strengthening family literacy practices is therefore essential to ensure children’s school readiness and long-term academic success.